2008
DOI: 10.1099/vir.0.2008/006957-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of human and avian metapneumoviruses

Abstract: Human (HMPV) and avian (AMPV) metapneumoviruses are closely related viruses that cause respiratory tract illnesses in humans and birds, respectively. Although HMPV was first discovered in 2001, retrospective studies have shown that HMPV has been circulating in humans for at least 50 years. AMPV was first isolated in the 1970s, and can be classified into four subgroups, A-D. AMPV subgroup C is more closely related to HMPV than to any other AMPV subgroup, suggesting that HMPV has emerged from AMPV-C upon zoonosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 50 publications
9
66
1
1
Order By: Relevance
“…Investigations of the evolutionary dynamics of HMPV and AMPV-C, using G, F, and N nucleotide sequences, demonstrated higher substitution rates for the G gene genes (56,259). Such high evolutionary rates are not uncommon for RNA viruses (120).…”
Section: Molecular Epidemiology and Virus Evolutionmentioning
confidence: 99%
“…Investigations of the evolutionary dynamics of HMPV and AMPV-C, using G, F, and N nucleotide sequences, demonstrated higher substitution rates for the G gene genes (56,259). Such high evolutionary rates are not uncommon for RNA viruses (120).…”
Section: Molecular Epidemiology and Virus Evolutionmentioning
confidence: 99%
“…1 Genomic and phylogenic analyses suggest that hMPV diverged from avian MPV, a virus that causes serious respiratory diseases in chickens. [15][16][17] Infection caused by hMPV presents a similar symptomatology as other respiratory viruses such as hRSV, parainfluenza virus and influenza, 18 whereby the diagnosis is difficult. Symptoms of hMPV include rhinorrhea, cough, acute otitis media, fever, and, less frequently, conjunctivitis, rash, diarrhea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…As there is a wider variety of AMPV subgroups compared with HMPV, it has been hypothesized that the direction of transmission was from birds to humans (de Graaf et al, 2008b). Therefore, it is of interest that HMPV did not replicate efficiently in QT6, QT35 (data not shown) and CEF cells (van den Hoogen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…AMPVs have been classified into four subgroups, A-D (Bayon-Auboyer et al, 1999;Eterradossi et al, 1995;Juhasz & Easton, 1994;Seal, 1998), and AMPV-C is more closely related to HMPV than the other AMPV subgroups (Govindarajan & Samal, 2004Govindarajan et al, 2004). It has been demonstrated that HMPV probably originated from birds and that a common ancestor of AMPV-C and HMPV existed around 200 years ago (de Graaf et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%